THE EMPOWERMENT OF PEOPLE’S PRIORITY ECONOMY BY CLUSTERING ECONOMIC SECTORSIN EAST KALIMANTAN PROVINCE (The Case Of 6 Regencies/Cities In East Kalimantan) - Arkas Viddy; Andi Syarifuddin; Zuhriah Zuhriah (Politeknik Negeri Samarinda, 2016)
Balikpapan, West of Kutai, East of Kutai, Paser, Bontang and Berau are the regencies/districts where located in East Kalimantan Province. Most of local communities in these regions can survive because of this resources by utilizing them. Unfortunately they still using a traditional method and lead their level of income is still low. For these reasons it needs to be designed the model of priorities clustering sectors which can improve the local communities income in East of Kalimantan. The main objective of this research is to build the economy cluster which can increase the local communities income in Tarakan City using diamond porter, Marketing analysis for creating the empowerment of local communities income in East Kalimantar. Others objectives are reflected as to analyze the factors to impact the Allocated Regional Budget (APBD) and the economic sector priorities in East Kalimantan and to analyze the economic sectors priorities using diamond model. The most economic sector priorities which local communities can involve to work in it areFishery and Agriculture which can be identified by involving of almost all family members and the amount of production. There are some obstacles in this business such as input e.g capital for Fishery and Agriculture fields. Lack of capital these businesses because in all of a loan proposal need to be followed by a certificate as a collateral, while they haven’t any certificate (land or house certificate). On the other hand, it is no significant influencese between regional economic indicators to the Allocated Regional Budget and the economic sector priorities except productive labor forces and the domestic investments. It means that the local government should be evaluated. The solution can be proposed are the local government should concern and focused on the local community obstaclessuch as to implement the apropriated aid or loan models for who involving in Fishery and Agriculture fields. The small business association system need to be established which all of the productions need to be collected by association and distribute it to the potential market with the good price. The association must provide a certainty amount of fund to be lent to the farmers and avoiding high rate cost of capital. Keyword : Economic, priority, sectors, clustering, allocated regional budget, labor forces and domestic investments.